Knowing, becoming, doing as teacher educators identity, intimate scholarship, inquiry - Hamilton, Mary Lynn.; Pinnegar, Stefinee E. (Bingley, U.K. : Emerald, 2015)
The Advances in research on teaching series was established to provide state-of-the-art conceptualization and analysis of the processes involved in functioning as a classroom teacher. These include not only the behaviors of teachers that can be observed in the classroom, but also the planning, thinking, and decision making that occur before, during, and after interaction with students.
Section overview : identity -- Definitions of identity -- Naming-and-being-named -- Pathways and experience -- Knowledge of a teacher educator -- Identity conclusion -- Disruption between identity and intimate scholarship -- Disruption : what's in a Name? Exploring the edges of autoethnography, narrative and self-study of teacher education practice methodologies -- Section overview : intimate scholarship -- The value of the particular -- Vulnerability -- Openness -- Dialogue as a tool for knowing -- Oriented toward the ontological -- Intimate scholarship conclusion -- Disruption between intimate scholarship and inquiry -- Disruption : scrutinizing trustworthiness in self-study of teacher education practices research -- Knowing through inquiry into experience -- Designing inquiry -- Attending to the process of inquiry in intimate scholarship -- Trustworthiness, coherence, rigor -- Inquiry conclusion -- Disruption between inquiry, conclusion, and international connections -- Disruption : forming, framing, and linking in developing research questions -- Final Summary.
Includes bibliographical references.
Print version record
Keywords: Education -- General; Education -- Teaching Methods & Materials -- General; Teaching skills & techniques; Teachers -- Training of; Educational research